Giving Effect to Refugee Children’s Fundamental Rights to Life and a Basic Education - Erika Serfontein (Obiter, 2019)
A gap in research on the violation of the rights of refugee children to well-being and education – both prerequisites for living a good life – has been recognised internationally as well as nationally. This article endeavours to partially fill this gap by (a) presenting a background to the situation of refugees in South Africa in general and refugee children in particular, (b) delineating relevant concepts, (c) explaining the international and national legislative framework applicable to refugee children, (d) clarifying the role of education in the life of refugee children, (e) identifying the various challenges such children present for an inclusive education system, as well as (f) drawing conclusions and making recommendations on overcoming these challenges.South Africa has experienced an overwhelming growth in refugees since its transition to democracy in 1994. In contrast to the 1951 Convention,1 which defines a refugee as someone who is incapable or reluctant to return to their country of origin owing to a justified fear of being oppressed on the grounds of race, religion, nationality, membership of a particular social group, or political opinion, studies found that refugees and their children from the rest of the African continent, as well as from as far afield as China, Bangladesh and Pakistan, mainly flee to this country to escape conditions of poverty, civil discord and even war in search of a better life. Instead of being welcomed, however, refugee children are often met with intimidation, hate, xenophobia, aggressive nationalism, exclusion and discrimination by South Africans on a daily basis.By concentrating on refugee children and probing the results of significant studies indicating the persistent challenges facing the realisation of inclusive education in South Africa, the author advocates a humanitarian approach to refugee children in order to respect their dignity whilst recognising their rights to life and a basic education within the borders of South Africa.